HYBRID CONSTELLATIONS: EXAMINING SOCIAL MEDIA’S ROLE IN THE MONTREAL LESBIAN SOCIAL SCENE - Duguay, Stefanie; Chartrand, Alex; Trépanier, Anne-Marie (AoIR Selected Papers of Internet Research, 2023)
This paper examines the role of social media in the definition and organization of lesbian sociocultural landscapes. Building from geographical studies that identify how lesbians’ dispersion across cities counters heteropatriarchal occupations of space, the study is anchored within Montreal/Tiohtià:ke to identify local approaches to visibility and gathering. This angle is combined with digital scholarship that considers how mobile technologies, platforms, and apps give rise to hybrid arrangements that merge physical and digital practices of socialization. These lenses are applied to interviews with representatives from organizations and individuals who use digital technologies to connect lesbians online and across physical space, such as for hosting parties, outdoor activities, and other social gatherings. Preliminary findings show that their use of social media facilitates negotiations of visibility and togetherness while posing definitional challenges. As Montreal’s lesbian networks have become dispersed across the city, multiple modes of communication–from email newsletters to social media–enable meeting across urban space. However, social media pages, events, and accounts necessitate the production of images and text that reflect static definitions of these organizations, the events, and their target audiences. Altogether, we find that social media is a focal tool, among others, to support lesbians’ networked social arrangements but that platforms lack affordances for the fluidity that is integral to ever-fluctuating lesbian/queer identities, locations, and temporalities.